Human response to habitat suitability during the Last Glacial Maximum in Western Europe. (30th January 2018) - Burke, Ariane; Riel‐Salvatore, Julien; Barton, C. Michael
ABSTRACT: This research takes a multi‐dimensional approach to the study of the archaeological record of Western Europe during the Last Glacial Maximum (LGM), combining two distinct components of the human adaptive system (technological organization and mobility) to test the impact of environmental variability on the mobility of Upper Palaeolithic groups. To this end we make use of two models. The first predicts landscape suitability as a function of a suite of environmental variables including topography, climate and inter‐annual climate variability. The second model explores the link between patterns of mobility and technological organization, using lithic retouch frequencies as a proxy for mobility strategies. Combining detailed environmental and lithic data allows us to derive a clearer picture of human adaptation to environmental conditions during a particularly rigorous climatic interval in Western Europe. Our results show that while foragers generally favoured more suitable habitats, logistical mobility strategies were deployed across a wide spectrum of habitat suitability. Residential mobility strategies, on the other hand, tend to occur in relatively less suitable and thus inherently more variable habitats. We conclude that foragers made use of a predominantly logistic strategy during the LGM while adopting more residential strategies in response to local and relatively short‐term fluctuations in the environment. The approach adopted here offers several promising avenues for future research on the ecology of human groups during the LGM.